Towards the collaborative improvement of research capacities essential for teacher education and practices in Serbia and Estonia (REP-synergy) - (:unkn) unknown (My University, 2025)
The request for a Preparatory Grant involves four partners (cf. below) and is aimed to finalize a submission for the Institutional Partnerships within the scientific co-operation program between Switzerland and two Eastern European countries – Estonia and Serbia. The Swiss institution, located at the University of Teacher Education (HEP-BEJUNE) in Biel/Bienne, is specialized in teacher education and related research studies, and has a tradition of collaboration within international programs including collaboration with Eastern Europe colleagues. The partner institution from Estonia is the Institute of Education of the University of Tartu that is mainly focusing on teacher education and related educational research. The institutional partnership will also involve two institutions from Serbia both from the University of Belgrade: the Teacher Education Faculty, specialized in theoretical methodological teacher education and professionally-applicative training, and the Institute of Psychology of the Faculty of Philosophy, specialized among other areas in educational researches. The main goal of the prospective Institutional Partnerships is to support partner institutions to strengthen relationships within the triangle consisted of educational research, teachers’ education and teachers’ practice (“REP-synergy” stands for Research-Education-Practice synergy). Our goal is not to establish a research project, but to open a possibility to fund scientific collaborations and promote synergies with the target countries in their endeavour to overcome the difficulties of the transition period. In particular, we intend to enhance qualitative research tradition (both in teacher preparation – mainly in terms of action research - and in doctoral studies – by introducing variety of qualitative approaches) in partner institutes. This issue has been identified as a crucial one in both Estonia and Serbia. The need to improve relevancy and applicability of research results to teachers’ education and educational practices is also a reality that calls Swiss scientists to establish strong relations with the society, and in particular within the educational field of teacher education. In our idea, the Institutional Partnerships will be a possibility to strengthen the paradigm that educational and psychological research should be firstly in service of practice (in opposition to the existing way of thinking research only for research purpose), and to enhance young researchers’ and future teachers’ research skills, mostly related to qualitative methods (but also mixed methods and some quantitative methods). How to reach these goals will be described in detail in the activity plan for the Institutional Partnerships. In general, we plan to organize different set of activities such as sessions of doctoral schools, workshops, and trainings in diverse methodologies (qualitative, quantitative and mixed) for future teachers and young researchers in order to foster collaboration between them. Besides providing training related to scientific approaches and research methods, we also emphasise the role of disseminating research results and their implications for practice. Through the Institutional Partnerships, we intend also to support staff and students’ mobility (through short visits, joint teaching activities) in order to improve institutional framework conditions that enable a further increase of the research performance in the different countries. The different competences of the Swiss applicant and partners will be the resources to offer a large and rich variety of methodological and epistemological topics to be afforded to the participants. Our respective practices of teaching and doing research in the three countries will be also put into dialogue in order to highlight how teaching practices and scientific research can be strongly interrelated and imply different processes (e.g. observing, doubting, analysing, modifying, informing, re-orienting) that can be pointed out in a set of activities involving future teachers and young researchers. The present request for a Preparatory Grant aims to obtain the possibility to organize a meeting in Switzerland in order to finalize and submit the application for the Institutional Partnerships program. The meeting that will be organized based on the preparatory grant will enable key representatives of all four partner institutions to meet together and to finalize jointly significant components of the submission for the Institutional Partnership (needs analysis, institutional strengths and capacities, main goals as well as concrete activities leading to goals achievement). In other words, the possibility to meet in Switzerland will be used to go further in the construction of a joint request towards the development of research capacities essential for teacher education and practices in Serbia and Estonia. The invited partners will be Nevena Budjevac (Teacher Education Faculty, University of Belgrade, Serbia), Äli Leijen (Institute of Education, University of Tartu, Estonia) and Aleksander Baucal (Faculty of Philosophy, University of Belgrade, Serbia). The main applicant, Francesco Arcidiacono (University of Teacher Education, HEP-BEJUNE, Switzerland) will organize the meeting and set the proper conditions to work with the partners in order to finalize and to submit the application for the Institutional Partnerships.
Keywords: not available